2015
DOI: 10.1016/j.adolescence.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of cannabis use initiation among high school students: Effects of social anxiety, expectancies, peers and alcohol

Abstract: This study identified protective and risk factors of cannabis use initiation, including expectancies and social anxiety. A questionnaire was completed twice by 877 teenagers. Logistic regressions, mediation and moderation analyses were performed. Significant risk factors were alcohol use, peer users, perceptual enhancement, and craving expectancies. Protective factors were negative behavior expectancies and social anxiety. Social anxiety protected from initiation through the mediating role of perceptual enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Research among socially anxious cannabis users suggests more cannabis use (despite experiencing cannabis-related problems) if cannabis-related problems were perceived as common and therefore presumably socially acceptable (Ecker, Richter, & Buckner, 2014). Moreover, perceptions of others’ use (reporting a greater number of friends who use cannabis), positive cannabis expectancies (e.g., enhancement), and social anxiety have been shown to predict cannabis use initiation among adolescents (Schmits, Mathys, & Quertemont, 2015). Perceptions of how others view risky cannabis use (e.g., approval or disapproval) are referred to as ‘injunctive norms.’ Studies have shown that cannabis injunctive norms are linked with behavior (Ecker & Buckner, 2014; LaBrie, Hummer, & Lac, 2011; LaBrie, Hummer, Lac, & Lee, 2010).…”
mentioning
confidence: 99%
“…Research among socially anxious cannabis users suggests more cannabis use (despite experiencing cannabis-related problems) if cannabis-related problems were perceived as common and therefore presumably socially acceptable (Ecker, Richter, & Buckner, 2014). Moreover, perceptions of others’ use (reporting a greater number of friends who use cannabis), positive cannabis expectancies (e.g., enhancement), and social anxiety have been shown to predict cannabis use initiation among adolescents (Schmits, Mathys, & Quertemont, 2015). Perceptions of how others view risky cannabis use (e.g., approval or disapproval) are referred to as ‘injunctive norms.’ Studies have shown that cannabis injunctive norms are linked with behavior (Ecker & Buckner, 2014; LaBrie, Hummer, & Lac, 2011; LaBrie, Hummer, Lac, & Lee, 2010).…”
mentioning
confidence: 99%
“…With regard to the first aim, contrary to the hypothesis, SA was found to be negatively related to cannabis use. Previous studies involving adolescent samples ( 9 11 , 45 , 46 ) showed that SA was a negative predictor of the risk of cannabis use and could therefore play a protective function. Although current findings may be to some extent limited by the cross-sectional nature of the study, is therefore likely that socially anxious youth, similar to adolescents, may use less cannabis because they are less likely to find themselves in peer context where cannabis use is common, probably due to their avoidant behavior.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, however, in the logistic model, perception of access to cannabis was neither a risk nor protective factor for initiation at the age of 13 years or younger. Perhaps, some social factors within the society which were not explored in this study exerted more powerful influences on when cannabis was initiated than perception of access did (20,22,24,25).…”
Section: Discussionmentioning
confidence: 96%